Viral Theatres' Pandemic Playbook - Documenting German theatre during COVID-19. Issue 1 (2nd January 2022) - Mosse, Ramona; Janke, Janina; König, Judith; Stein, Christian; Tecklenburg, Nina
ABSTRACT: This document offers an overview of the artistic research project Viral Theatres, which documents the radical changes in theatre aesthetics and infrastructure during the Covid-19 pandemic by building an online multimedia living archive that tracks these developments in interviews, video documentaries, rehearsal residencies, and case studies. Through a survey of five exemplary case studies we show how significantly the tools and practices of theatre have shifted during the pandemic and suggest that these examples belong to a reconceptualization of the idea of theatre per se . In creating an online Living Archive platform that makes these and other case studies and pandemic material accessible, Viral Theatres contributes to creative documentation of pandemic culture.